2015
DOI: 10.1134/s0030400x15060144
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence characteristics of the Kr2F* excimer molecules in (Kr-SF6) gas mixtures with a Low SF6 content upon pumping by a pulsed beam of fast electrons

Abstract: Emission spectra of dense Kr + SF 6 gas mixtures with different composition excited by a pulsed beam of fast electrons are measured. The electron energy is 150 keV, and the amplitude and duration of a beam current pulse are 5 A and 5 ns. The composition of gas mixtures was Kr (190-1900) Torr and SF 6 (0.1-1.0) Torr. The efficiency of formation of excimer Kr 2 F* molecules was found to be high in dense (~1 atm) Kr-SF 6 mixtures with a low SF 6 donor content. The luminescence times and quenching constants of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Our research has shown that Ar-Xe-CCl 4 and Xe-CCl 4 gas mixtures of a high pressure with a low concentration of CCl 4 molecules are of particular interest. When these gas mixtures were pumped by nuclear particles, an effective population was observed in the B, C and 4 2 Г states of the excimer molecules XeCl* and Xe 2 Cl* in this condition [13][14][15][16][17].…”
Section: Nuclear Excited Plasma and Formation Of The Excimer Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research has shown that Ar-Xe-CCl 4 and Xe-CCl 4 gas mixtures of a high pressure with a low concentration of CCl 4 molecules are of particular interest. When these gas mixtures were pumped by nuclear particles, an effective population was observed in the B, C and 4 2 Г states of the excimer molecules XeCl* and Xe 2 Cl* in this condition [13][14][15][16][17].…”
Section: Nuclear Excited Plasma and Formation Of The Excimer Moleculesmentioning
confidence: 99%
“…We conducted experimental studies of luminescence of halogen-containing rare-gas molecules upon the excitation of a dense (~ 1 atm) gas mixture by fast electrons with the energy of 150 keV and uranium fission fragments (Е f~ 70 MeV). It was found that to obtain an effective action of an excimer laser on the В-Х, С-А or 4 2 Г-1 2 Г transitions of molecules XeCl*, XeBr*, XeI*, KrF*, Xe 2 Cl*, Kr 2 F, Xe 2 I*, it is necessary to maintain a low concentration of halogencontaining molecules in the gas mixture compared to the concentration of electrons in a track of a nuclear particle [13][14][15][16][17]. This is due to the properties of a track structure of plasma created by high-energy charged particles: all the kinetic energy of a charged particle in a dense medium stands out in a narrow region of space along the particle's trajectory with characteristic dimensions of about 1 micron in diameter and about several centimeters long [18].…”
Section: Introductionmentioning
confidence: 99%